SIMBOL AIR BAPTIS: RAHMAT YANG DITERIMA OLEH UMAT ALLAH MELALUI PEMBAPTISAN - Noch, Glaudio; Melsadalim, Sandi Moses (Pineleng Theological Review, 2025)
Baptism is a very important sacrament in the lives of Catholics, and the water of baptism is a symbol rich in meaning. Through the water of baptism, God's people receive grace and salvation, and experience a process of renewal and new birth. This article will discuss the meaning of the symbol of baptismal water in Scripture, Church teachings, and also seen in the rite of blessing the water of baptism during the Easter Vigil. It will also discuss how God's grace is received by God's people through baptism. By understanding the symbol of baptismal water, Catholics can better appreciate the meaning of baptism and experience God's grace in their daily lives. This discussion will cover the theological, historical, and pastoral aspects of baptism, as well as its implications for the lives of the faithful.